Comparative study on proximate and mineral composition of native and hybrid pangas (Pangasius pangasius, P. hypophthalmus) at raw and fried stages (Journal of the Asiatic Society of Bangladesh, Science, 2021)
A study was conducted on the proximate and mineral composition of native and hybrid pangas, namely Pangasius pangasius and Pangasius hypophthalmus at raw and fried stages between January and December 2017. At the raw stage higher amount of average protein (23%) found in native pangas compared to hybrid (19.7%) and hybrid pangas contain higher fat (15.95%) compared to native (12.75%), although the moisture content was the same in both. Protein and fat were higher in both fishes at 26.8% and 20.95% in natives and 24.05% and 24.2% in hybrids at the fried stage. At the raw stage, mineral contents were higher in natives and the highest content was sodium (185.38 mg/100 g) followed by phosphorus (166.90 mg/100 g) and calcium (116.35 mg/100 g) and slightly decreased those minerals at the fried stage of the same fish. In the fried stage, mineral contents were found almost the same, although calcium, magnesium, iron was slightly varied and phosphorus, sodium found high in amount. But energy level was higher (328 Kcal) in hybrids compare to native. Thus, the study of raw and fried stages indicates that native pangas are better in proximate and mineral composition than the hybrids, but the energy was high in hybrids.J. Asiat. Soc. Bangladesh, Sci. 47(1): 13-22, June 2021